Effect of aggregate size and inclusion of polypropylene and steel fibers on explosive spalling and pore pressure in ultra-high-performance concrete (UHPC) at elevated temperature - Li, Ye (2021)
This paper investigates the individual and combined effects of polypropylene (PP) fibers, steel fibers, and aggregate size on spalling behavior and pore pressure build-up of ultra-high-performance concrete (UHPC) exposed to elevated temperature. Simultaneous measurements of pore pressure and temperature were conducted at different depths in UHPC specimens under one-sided heating with a heating rate of 2 °C/min. Compressive, tensile, and permeability tests were performed to analyze spalling behavior. Addition of PP fibers fully prevented spalling and they are much more effective in increasing permeability than steel fibers and larger aggregates. The combined use of PP and steel fibers, and PP fibers and larger aggregates showed strong synergistic effect on increasing permeability. The higher the permeability, the lower was the maximum pore pressure measured in the samples. Two plateaus were observed from the temperature history due to vaporization of liquid water (between 115 and 125 °C inside the specimens) and release of water vapor (starting from 180 °C), respectively. The second plateau was identified as the functional temperature of PP fibers. Maximum pore pressures in spalled specimens were much lower than their tensile strengths, which could imply the contribution of hydraulic pressure in the region of moisture clog on spalling.